2018
DOI: 10.1097/01.blo.0000533626.25502.e1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Anteroinferior Iliac Spine: Is the Subspine Pathologic? A Clinical and Radiographic Evaluation

Abstract: Level III, diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Hetsroni et al (9) reported higher association of SSI with type II and type III AIIS by showing reduced hip flexion and internal rotation in these patients. Other studies found no correlation between AIIS morphologic characteristics and the SSI (11,27), and, similar to our research, some studies found a greater frequency of type I AIIS in their cohort with SSI (10,12). The elevated range of hip flexion and reduction in femoral anteversion have been attributed as predisposing factors for SSI independent of AIIS types (10,12).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Hetsroni et al (9) reported higher association of SSI with type II and type III AIIS by showing reduced hip flexion and internal rotation in these patients. Other studies found no correlation between AIIS morphologic characteristics and the SSI (11,27), and, similar to our research, some studies found a greater frequency of type I AIIS in their cohort with SSI (10,12). The elevated range of hip flexion and reduction in femoral anteversion have been attributed as predisposing factors for SSI independent of AIIS types (10,12).…”
supporting
confidence: 87%
“…Although numerous studies have described FAI imaging findings, few have focused on the association between symptoms and morphologic characteristics of AIIS, AIIS distance to the acetabular rim, and rectus femoris footprint (3,5,7,9,10). The role of AIIS as the only cause for SSI has also been questioned (11), and recent studies showed that SSI can occur in all types of AIIS, including normal AIIS (type I) (8,12).…”
mentioning
confidence: 99%
“…1 Subsequently, studies have described a subspine classification system, anatomic footprint, and clinical outcomes after arthroscopic subspine decompressions. [1][2][3][4][5][6] Despite this literature, there are still questions regarding the prevalence, existence, and whether or when decompression of the AIIS should be considered.…”
Section: See Related Article On Page 91mentioning
confidence: 99%
“…However, other authors have proposed that Type 1 hips may cause impingement against the distal femoral neck during excessive hip flexion, as is seen in ballet and high kick dancing ( 11 ). Meanwhile, the investigation by Karns et al ( 30 ) retrospectively analyzed AIIS morphology in 145 patients on anteroposterior and false profile radiographs, reporting no correlation between hip flexion, and internal rotation based on the AIIS classification type proposed by Hetsroni et al ( 10 ) Moreover, Balazs et al ( 31 ) found no difference in the distribution of Type 1 vs. Types 2 and 3 AIIS morphology when comparing symptomatic and asymptomatic patients, further questioning the association of AIIS in morphology in clinical extra-articular hip impingement. In addition, the authors reported difficulty distinguishing between Type 1 and Type 2 morphologies due to the confluence of the ilium wall and acetabular rim resulting in a lack of a distinct separation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%